Analysis of Effect on Asset Return, Return on Equity, Earning Per Share, and Net Profit Margin on Share Price on Banking Company - Agnes Claudia; Menik Indrati (Publikasi Indonesia, 2021)
The purpose of this study was to analyze the effect of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM) on stock prices. In this study, there is one dependent variable, namely stock prices, and four independent variables, namely Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM). Return on Assets (ROA) is measured by dividing net income by total assets in the company. Return On Equity (ROE) with return on common equity and net return on common equity, which measures the return on investment of ordinary shareholders. Net Profit Margin (NPM) is calculated by dividing the total net profit earned by the company by each sale made. Earning Per Share (EPS) by dividing the number of each ordinary share produced during a specific period by the shares outstanding, measured by dividing the total period income available to shareholders from the company's common shares by the number of ordinary shares outstanding. The population and sample are 35 companies with banking companies listed on the Indonesia Stock Exchange during 2017 – 2019, so that the research sample is 35 samples, namely 105 companies. The results of this study indicate that Return On Assets (ROA) does not affect stock prices, Return On Equity (ROE) is detrimental to stock prices, Earning Per Share (EPS) has a positive effect on stock prices, and net income. Margin (NPM) does not affect stock prices.